CAN THE CIPP MODEL EVALUATION BE APPLIED TO HIGH SCHOOLS OR VOCATIONAL SECONDARY SCHOOLS?: EVALUATION STUDY AT SMA NU GRESIK - Dian Oktaviana; Budi Purwoko; Najlatun Naqiyah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This article endeavors to delve into the intricacies of human psychology within the framework of the Quran and Hadith. The research methodology employed is a comprehensive library research approach, utilizing reputable sources such as books, journals, and pertinent prior research related to the predetermined theme. The research findings illuminate that the field of psychology delves into the very essence of the human soul, exploring various phenomena, processes, and contextual backgrounds. Viewing humans from the perspective of individual and social entities, encompassing the psychological (spiritual) and biological dimensions, they are perceived as entities harmonizing both material and spiritual components. Within the context of their relationship with the Divine, humans are esteemed as servants (makhluq) holding the highest position. The comprehension of human psychology in the Islamic perspective is elucidated through the conceptual exploration of Nafs, al-Aqlu, al-Qalbu, and ar-Ruh.Amit, A., & Sagiv, L. (2013). The PreferenSort: A holistic instrument for career counseling. Journal of Career Assessment, 21(2), 249–264.Astika, G. N. (2021). Meningkatkan Kemampuan Guru BK SMA dalam Pelaksanaan Layanan Bimbingan Klasikal Melalui Supervisi Klinis. Jurnal Ilmiah Bimbingan Konseling Undiksha, 12(1). https://ejournal.undiksha.ac.id/index.php/JIBK/article/view/32596Badrujaman, A. (2012). Faktor-Faktor Yang Mempengaruhi Keterlaksanaan Evaluasi Program Bimbingan dan Konseling. Perspektif Ilmu Pendidikan, 26(XVII), 131–137. https://journal.unj.ac.id/unj/index.php/pip/article/view/6895/4980Budiman, C., Badrujaman, A., & Wahyuni, E. (2022). Evaluasi Program Bimbingan dan Konseling Bidang Sosial dengan Teknik Contex, Input, Proses, Produk (CIPP) di Sekolah Menengah Kejuruan. Jurnal Konseling Dan Pendidikan, 10(2), 354. https://doi.org/10.29210/181300Devi Sri Raso Tampubolon, P., Anneke Rantung, D., & Naibaho, L. (2023). KAJIAN PENTINGNYA BELAJAR MENGEVALUASI PELAKSANAAN PEMBELAJARAN MENGGUNAKAN MODEL EVALUASI CIPP. EDUSAINTEK: Jurnal Pendidikan, Sains Dan Teknologi, 10(2), 582–599. https://doi.org/10.47668/edusaintek.v10i2.757Dicky Artanto, Hasan Ibadin, & Suwadi. (2023). Penerapan Evaluasi CIPP (Context, Input, Process,Product) Dalam Program Rintisan Madrasah Unggul Di MTsN 1 Yogyakarta. Al-Fahim : Jurnal Manajemen Pendidikan Islam, 5(1), 68–82. https://doi.org/10.54396/alfahim.v5i1.543Hakan, K., & Seval, F. (2011). CIPP evaluation model scale: development, reliability and validity. Procedia-Social and Behavioral Sciences, 15, 592–599.Hidayah, N. (2012). Process-Audit dalam Penyelenggaraan Pendidikan Akademik Jenjang S-1 Bimbingan dan Konseling. Jurnal Pendidikan Dan Pembelajaran (JPP), 17(2), 129–139.Hoshmand, L. T. (2004). The Transformative Potential of Counseling Education. The Journal of Humanistic Counseling, Education and Development, 43(1), 82–90. https://doi.org/10.1002/j.2164-490X.2004.tb00045.xIsriyah, M. (2023). KUALITAS LAYANAN BIMBINGAN KONSELING: PERAN SUPERVISOR DALAM PENINGKATAN MUTU. Psikodidaktika: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan Dan Konseling, 8(2), 465–473. https://doi.org/10.32663/psikodidaktika.v8i2.4128Kamilia, F. F. S., Wahyudin, D., & Dewi, L. (2023). CIPP evaluation model: E-learning based life skills training. 060001. https://doi.org/10.1063/5.0111265Kasmaini, K., Hamzah, S., & Winarto, H. (2023). CIPP Evaluation Model: Online In-service Teachers Training Program Conducted at English Language Education Study Program of Bengkulu University. ENGLISH FRANCA : Academic Journal of English Language and Education, 7(1), 105. https://doi.org/10.29240/ef.v7i1.5871Kemendikbud. (2016). Panduan Penyelenggaraan Bimbingan dan Konseling pada Pendidikan Dasar dan Pendidikan Menengah. Jakarta.Kui, H. (2023). Education Quality Evaluation Method Based on CIPP Theory (pp. 1200–1207). https://doi.org/10.1007/978-981-99-1428-9_155Kurniawati, E. W. (2021). Evaluasi Program Pendidikan Perspektif Model CIPP (Context, Input, Process, Product). GHAITSA: Islamic Education Journal, 2(1), 19–25. https://siducat.org/index.php/ghaitsa/article/view/168Lathifah, M., & Wirastania, A. (2022). Implementasi Supervisi Klinis Terhadap Keterampilan Konseling Individu Pada Mahasiswa Program Studi Bimbingan dan Konseling. Jurnal Fokus Konseling, 8(1), 52–57. https://doi.org/10.52657/jfk.v8i1.1557Maulana, C., Astuti, I., & Wicaksono, L. (2019). Evaluasi Program Layanan Informasi Dengan Model CIPP di SMP Negeri 14 Pontianak. Jurnal Pendidikan Dan Pembelajaran Khatulistiwa, 8(9). https://doi.org/10.26418/jppk.v8i9.35511Mujiyati, M., Mayasari, S., & Adiputra, S. (2020). A comparison of accountability models in school counseling programs. Konselor, 9(3), 117–124. https://doi.org/10.24036/0202093110561-0-00Muyana, S. (2017). Context Input Process Product (CIPP): Model Evaluasi Layanan Informasi. Prosiding Seminar Bimbingan Dan Konseling, 1(1), 342–347.Pambudi, Y. E., & Amini, S. N. K. (2021). Peran Kepala Sekolah Terhadap Manajemen Guru Bimbingan dan Konseling di Masa Pandemi. Edu Consilium: Jurnal Bimbingan Dan Konseling Pendidikan Islam, 2(2). https://doi.org/10.19105/ec.v2i2.4983Pujiastuti, P., Herwin, H., & Firdaus, F. M. (2021). Thematic Learning during the Pandemic: CIPP Evaluation Study. Cypriot Journal of Educational Sciences, 16(6), 2970–3980. https://doi.org/10.18844/cjes.v16i6.6481Rahmawati, R., Neviyarni, N., & Firman, F. (2016). Hubungan Motivasi Kerja dan Dukungan Sosial Kepala Sekolah dengan Pelaksanaan Tugas Guru BK di SMPN Kab. Kerinci. Konselor, 3(3), 94–100.Ratnaya, G., Indriaswuri, R., Widayanthi, D. G. C., Atmaja, I. M. P. D., & Dalem, A. A. G. P. K. P. (2022). CIPP Evaluation Model for Vocational Education: A Critical Review. Education Quarterly Reviews, 5(3). https://doi.org/10.31014/aior.1993.05.03.519Santosa, I., Setiadi, S., & Suseno, M. (2022). CIPP evaluation on emergency online learning during Covid-19 in STKIP MNC. Linguists : Journal Of Linguistics and Language Teaching, 8(2), 169. https://doi.org/10.29300/ling.v8i2.6400Siregar, S. K., Lubis, S. A., & Syukri, M. (2023). EVALUASI PROGRAM BIMBINGAN KONSELING DI SMK PENERBANGAN PBD MEDAN. Research and Development Journal of Education, 9(2), 977–989. https://doi.org/10.30998/rdje.v9i2.19515Sopha, S., & Nanni, A. (2019). The CIPP Model : Applications in Language Program Evaluation. The Journal of AsiaTEFL, 16(4), 1360–1367. https://doi.org/10.18823/asiatefl.2019.16.4.19.1360Stufflebeam, D. L. (2004). The 21st century CIPP model. Evaluation Roots, 245–266.Stufflebeam, D. L. (2007). CIPP evaluation model checklist.Stufflebeam, D. L., & Zhang, G. (2017). The CIPP Evaluation Model How to Evaluate for Improvement and Accountability. Guilford Publications.Thayyibah, J. (2020). Evaluasi Pelaksanaan Layanan Informasi Bidang Karir dengan Menggunakan Model CIPP pada Siswa Kelas XII Teknik Geomatika di SMK Negeri 5 Banjarmasin. Jurnal Pelayanan Bimbingan Dan Konseling, 2(2).Utomo, S. B., Atma, E. S., Dwikurnaningsih, Y., & Loekmono, J. T. L. (2023). EVALUASI PROGRAM BIMBINGAN DAN KONSELING BERBASIS CIPP PADA MASA PANDEMI COVID-19. Satya Widya, 39(1), 40–50. https://doi.org/10.24246/j.sw.2023.v39.i1.p40-50Warju, W. (2016). Educational Program Evaluation using CIPP Model. INVOTEC, 12(1). https://doi.org/10.17509/invotec.v12i1.4502